Research on Nutrition, Dental Caries Status Using Novel Methods, and Related Factors to Preschool Children in Rural Areas of Vietnam - Do Hong Cuong; Vu Van Tam; Hoang Quy Tinh; Le Thanh Do; Nguyen Trong Nghia; Hoang Cong Anh (Journal of Analytical Methods in Chemistry)
The study aims to examine correlations between nutrition status with different factors and dental caries of preschool children in rural areas of Vietnam. A big data based on a total of 690 children (356 boys and 334 girls), aged 2–5 years, living in Van Xuan commune, were thoroughly analyzed. Oral examinations were performed by dentists with the assistance of nursery teachers and the research team. Caries was diagnosed using criteria established by the International Caries Detection and Assessment System (ICDAS). The examined children and their parents responded to questions pertaining to dental hygiene practices. The nutrition status of preschool children was determined by the World Health Organization (WHO) standards in 2006. There are factors which have effects on the malnutrition status of children in the research. The prevalence of dental caries also contributed importantly to assess children’s development. In this study, the stunting groups have a higher ratio of caries compared to the others. Children’s morphology and nutritional status are associated with dental caries among the preschool children in Van Xuan commune, Vinh Tuong district, Vinh Phuc province.